(3LGeY GdHjGf aj JChjd Bj GdaQbGfs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg CKfGA JaSjQ GdBjI GdcQjeI (B" (3ef Ohfg acjhfi LejYkG Ke dGJfXQhf (B" (3Hbhdg (B: (3jbhd aGMJGdhG CfJe LejYkG hCdgJce s
(3BNQgG (B:s
(3jfJgi HEfJgGA GdShQI HGdbhd ai JChjd bhdg JYGdi (B" (3hddg ZjH GdSehGJ hGdCQV hEdjg jQLY GdCeQ cdg W Yf cYH bGd NGJeI GdJhQGI NGJeI ghO s
(3bWYI efg ai JaSjQ ShQI ghO s
(3Ydi Qb ZRGd s
(3ef JMHjS GdSdWGf CHj YHO Gddg GdefJUQ GdeQjfi HJGQjN (B827 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs